Synthesis methods for β-belite using lime sludge and silica particles - Maheswaran, S.; Kalaiselvam, S.; Palani, G.S.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
The objective of this study is to compare the methods of synthesis β-phase belite by using lime sludge (LS), a residual solid generated from paper and pulp industry with nano silica (NS) and silica fume (SF). The precursor study shows that LS and calcined lime sludge (CLS) are not generally pozzolanic, but mainly CaCO3/CaO. Three synthesis methods viz., hydrothermal-calcination route, solid state reaction, and mechanochemical are used for the synthesis of belite. Ca/Si molar ratio of 2.0 is used for all the methods. About 94% of pure belite is obtained by solid state reaction method, followed by mechanochemical and hydrothermal methods. The results show that latter two methods consumes more energy by means of calcination of LS, whereas the former consumes less energy. In addition, hydrothermal method with CLS and SF requires water for the chemical reactions and higher sintering temperature of about 1000°C. However, in all the methods, the belite is synthesized without use of any chemical stabilizers. The micro-analytical characteristic features of the raw material, intermediate products and the formed belite are analyzed qualitatively and quantitatively by means of XRD, XRF, TG-MS-DTA, SEM, FT-IR and BET techniques appropriately. Hence, this study leads to novel development of comparatively low-energy cementitious composite materials for future potential applications in the construction field.